Influence Of Media Collaboration With Stakeholders In The Prevention Of Illegal Gold Mining In Zamfara, Nigeria - Naziru, Alhaji Tukur (2022)
This study aims to investigate the elements that contribute to illegal gold mining (IGM) in Zamfara, Nigeria, as well as the duration, integration, and commitment of the media, government agencies, non-governmental organisations, and community leaders in collaborating to prevent IGM.